Effectiveness of Proprioceptive Neuromuscular Facilitation, Sensorimotor Training and Conventional Exercise Along With Whole Body Vibrator on Balance in Patients with Diabetic Peripheral Neuropathy (International Journal of Physiotherapy, 2024)
Background: Diabetic peripheral neuropathy is one of the most common complications of patients with type 2 diabetes mellitus. The study's objective was to find the comparative effects of proprioceptive neuromuscular facilitation, sensorimotor training, conventional exercise, and whole body vibrator on balance in patients with diabetic peripheral neuropathy.Methods: This was an experimental study of comparative type with 60 subjects. The study was carried out at the Faculty of Physiotherapy department, Dr. M.G.R. Educational and Research Institute, for eight weeks after its approval from the institution's review board. Clinically diagnosed diabetic mellitus patients aged 45 to 60 years were selected for the study for the last seven years. The selected participants were divided into three groups using a random sampling method. Michigan neuropathy screening instrument, berg balance scale, and Time up and test were used to assess before and after the intervention.Results: In this study, the comparative effect of Whole Body Vibrator with PNF Training, Whole Body Vibrator with sensory motor Training, and Conventional Training on MNSI, BBS, and TUG4 shows a significant difference in the Post-test of MNSI and TUG but no difference in BBS between Group A, B and C with P value